What competitions were conducted in the service categories of the World Robot Summit?. (2nd September 2019) - Okada, Hiroyuki; Inamura, Tetsunari; Wada, Kazuyoshi
Abstract : The World Robot Summit is a competition held to realize a world where humans and robots can cooperate and coexist. The WRS Service Categories are competitive events which, with 'cooperation between human and robot' as their important theme, present robot technology competitions designed, mainly, to enable people and robots to cooperate with and complement each other, as they will be required to do so in homes, shops, and other living spaces. In this paper, we described the details of three competitions, the Partner Robot Challenge (Real Space), Partner Robot Challenge (Virtual Space and Future Convenience Store Challenge which conducted in the WRS Service Category. GRAPHICAL ABSTRACT: